(untitled) (BALEAP Journal of Research and Practice, 2025)
The write-up reflects on the practice observed in the EAP module of one of the transnational higher education institutions in Tashkent (Uzbekistan). Initially, the EAP module aimed to develop the learners’ language proficiency further; however, at the request and suggestions of the subject lecturers and different stakeholders, graduate attributes were enhanced in the module learning outcomes. Consequently, the focus and assessment tasks shifted from implementing the Study Skills, Academic Socialisation and to Academic Literacies models (Lea & Street, 2006). If, in the past, the EAP lessons targeted teaching grammar, vocabulary, and the development of language skills needed for academia, at present, they address teaching language skills and developing soft, academic, and research skills.